Latin america and strategic options: an analysis of extra-regional relations (2011)
The primary purpose of this paper is to analyze a particular aspect of foreign policy in Latin America: extraregional relations. In this direction, we will try to elucidate the existence of different models of foreign policy among Latin American nations, the general condition of the existing links between Latin America and the United States and the extent of extra-hemispheric integration in the region. This will specify how much continuity and novelty characterizes the international behavior of countries in the area. This, in turn, will help you understand how it has changed American foreign policy in recent years and how the observables on that front means a longer lasting trend of structural changes linked to international and domestic developments or express a temporary situation provided by global changes and internal fluctuations.